The Use of Low Intensity Laser in Wound Healing in Dog - Rodrigues, Denise de Fátima; Iori, Isabela de Mello; Rodrigues, Karina Squincalha; Santos, Kaike Gomes dos; Silva, Isabella Stange Ribeiro da (Acta Scientiae Veterinariae, 2021)
Background: Low-intensity laser is effective in cellular metabolism, analgesia, and tissue repair. The bioelectric, bioenergetic, and biochemical effects of laser therapy stimulate local circulation, collagen formation, and epithelization. The objective of this study was to report the use of gallium-aluminum arsenide (GaAlAs) laser (830 nm) in healing two wounds caused by necrosis in a dog. Case: An 8-year-old bitch, a rescued victim of animal abuse, had tibiotarsal dislocation in the left posterior limb. Orthopedic surgery was performed with the placement of an external fixation device with six pins in the distal third of the left posterior limb. A radiographic examination performed 42 days after the surgery revealed the loss of the tibiotarsal ratio, decreased radiopacity of the carpal bones, edema, inflammation, muscle atrophy, and the rotation of the anatomical axis of the metatarsals and phalanges. It was then decided to perform a second orthopedic surgery, in which a bone graft and arthrodesis with an 8-screw titanium plate were performed. Four of the plate screws were placed proximally to the tibia and four distally to the tarsus in addition to a screw and a pin transfixed through the distal metaphyseal region of the tibia and calcaneus. Traction was felt during suturing in the dermis and epidermis of the limb, suggesting the possibility of dehiscence of the stitches. After 3 h of surgery, the limb was cold and edematous. After 5 days, the tissue of the medial region of the tarsus developed necrosis, exposing a wound 6 cm long, 1.5 cm wide, and 2 mm deep (wound 1). Another necrotic lesion was observed in the dorsal region of the tarsos - 6.5 cm long, 2 cm wide, 3 mm deep, and exposing 5 cm of the titanium plate (wound 2). Therapy with GaAlAs laser was then performed over the entire length of the wounds. In each therapeutic session, the laser was first used in punctual mode at 10 J/cm², 830 nm, 20 s at each point of the length of the lesion and then in scan mode at 10 J/cm², 830 nm, 1000 Hz, and 40 s continuously. Laser therapy sessions were conducted at 2-4 day intervals, with a 12-day interval between the eighth and ninth sessions. During the entire treatment, cleansing and debridement of the wounds were performed every 48 h with saline and chlorhexidine digluconate, using a compression bandage, as described earlier. Wound 1 healed completely after two laser therapy sessions. In wound 2, tissue repair stagnated after the ninth and last laser session, leaving 4 cm of the titanium plate still exposed. The limb could not support the body weight of the patient, and radiographic examination revealed that the anatomical axis of the metatarsals and the phalanges was rotated and bone conformation was poor. Given the anatomical conditions associated with the patient's clinical picture, it was decided to amputate the limb between the femur and tibia. Discussion: Therapeutic lasers act on mitochondrial respiration, increasing respiratory metabolism and stimulating DNA synthesis and tissue proliferation. In the present case, there was a decrease in inflammatory cells, edema, and the size of the wounds. The pathological conditions of the affected site, influence of trauma, and degree of tissue damage affected the results of the laser therapy. Despite the size difference between wounds 1 and 2, the exposed titanium plate was a determining factor for the partial healing of wound 2. Keywords: laser, laser therapy, scar, necrosis, orthopedics, physical therapy, tissue repair. Título: A utilização do laser de baixa intensidade na cicatrização de ferida em cão. Descritores: laser, laserterapia, cicatriz, necrose, ortopedia, fisioterapia, reparo tecidual.